Susceptibility artifacts detected on 3T MRI of the knee: frequency, change over time and associations with radiographic findings: data from the Joints on Glucosamine Study - Jarraya, M.; Hayashi, D.; Guermazi, A.; Kwoh, C. K.; Hannon, M. J.; Moore, C. E.; Jakicic, J. M.; Green, S. M.; Roemer, Frank (Osteoarthritis and Cartilage, 2014)
To determine the prevalence of intraarticular susceptibility artifacts and to detect longitudinal changes in the artifacts, on 3T magnetic resonance imaging (MRI) of the knee in a cohort of patients with knee pain, and to assess the association of susceptibility artifacts with radiographic intraarticular calcifications.Three hundred and forty-six knees of 177 subjects aged 35-65 were included. 3T MRI was performed at baseline and at 6 months. Baseline radiographs were assessed for presence/absence of linear/punctate calcifications within the tibiofemoral joint (TFJ) space. Corresponding MRIs were assessed for susceptibility artifacts (i.e., linear/punctate hypointensities) in the TFJ space on coronal dual-echo steady-state (DESS) sequences. Kappa statistics were applied to determine agreement between findings on baseline DESS and radiography. Changes in artifacts over time were recorded.In the medial compartment, 13 (4%) of the knees showed susceptibility artifacts at baseline. Six knees had persistent artifacts and six knees had incident artifacts at follow-up. Agreement between DESS and radiography was ? = 0.18 (-0.15, 0.51) in the medial compartment. Frequency of artifacts in the lateral compartment was low (2%).Susceptibility artifacts detected on knee MRI are not frequent, and likely correspond to vacuum phenomena as they commonly change over time and are not associated with intraarticular calcifications. Radiologists should be aware of these artifacts as they can interfere with cartilage segmentation.
EVALuna2:14459